The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1103/physrevd.94.115017
|View full text |Cite
|
Sign up to set email alerts
|

Natural generalized mirage mediation

Abstract: In the supersymmetric scenario known as mirage mediation (MM), the soft SUSY breaking terms receive comparable anomaly-mediation and moduli-mediation contributions leading to the phenomenon of mirage unification. The simplest MM SUSY breaking models which are consistent with the measured Higgs mass and sparticle mass constraints are strongly disfavoured by fine-tuning considerations. However, while MM makes robust predictions for gaugino masses, the scalar sector is quite sensitive to specific mechanisms for m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
97
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(103 citation statements)
references
References 85 publications
(81 reference statements)
4
97
0
Order By: Relevance
“…A nice review of the status of dark matter SUSY searches in different supersymmetric scenarios with neutralino dark matter can be found in Ref. [13]. In any case, the recent prospects exposed by the LUX [14] and FERMI [15] collaborations showed that the WIMP paradigm should be excluded (or discovered) for dark matter masses below 10 TeV in the present generation of detectors.…”
Section: Introductionmentioning
confidence: 99%
“…A nice review of the status of dark matter SUSY searches in different supersymmetric scenarios with neutralino dark matter can be found in Ref. [13]. In any case, the recent prospects exposed by the LUX [14] and FERMI [15] collaborations showed that the WIMP paradigm should be excluded (or discovered) for dark matter masses below 10 TeV in the present generation of detectors.…”
Section: Introductionmentioning
confidence: 99%
“…to require relatively large fine-tuning in light of the measured value of the Higgs boson mass [64], led us to suggest a phenomenological generalization of this picture discussed in section 2 [65]. This extension allows us to accommodate the mass patterns suggested by the mini-landscape picture mentioned above, the phenomenology of which is the subject of this paper.…”
Section: Jhep06(2017)101mentioning
confidence: 90%
“…Phenomenology of the mirage mediation have been studied before the Higgs boson discovery [16][17][18] and after the discovery [19][20][21][22][23]. The mirage mediation in the Next-to-MSSM 2 has been also studied in refs.…”
Section: Jhep11(2017)189mentioning
confidence: 99%